Adult Antiretroviral Therapy and Child Health: Evidence from Scale-up in Zambia - Lucas, Adrienne M; Wilson, Nicholas L (American Economic Review, 2013)
One in five Zambian children lives with an HIV/AIDS-infected adult. We estimate the effect that the availability of adult antiretroviral therapy (ART) has on the health of such children. Using a triple difference specification, we find that adult access to ART resulted in increased weight-for-age and decreased incidence of stunting among children younger than 60 months who resided with an infected father or other infected adult in an intact household. Because the increased availability of adult ART in sub-Saharan Africa has multigenerational effects, cost-effectiveness estimates restricted to direct recipients understate the economic benefit of the treatment.